2020
DOI: 10.1038/s41398-020-00987-z
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Identification of de novo mutations in prenatal neurodevelopment-associated genes in schizophrenia in two Han Chinese patient-sibling family-based cohorts

Abstract: Schizophrenia (SCZ) is a severe psychiatric disorder with a strong genetic component. High heritability of SCZ suggests a major role for transmitted genetic variants. Furthermore, SCZ is also associated with a marked reduction in fecundity, leading to the hypothesis that alleles with large effects on risk might often occur de novo. In this study, we conducted whole-genome sequencing for 23 families from two cohorts with unaffected siblings and parents. Two nonsense de novo mutations (DNMs) in GJC1 and HIST1H2A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…In schizophrenia (SCZ) patients, nonsense de novo mutations of ZNF595 are common. Data from genome-wide association studies suggested that common variants in the ZNF595 gene may be associated with SCZ and SCZ-related traits [30]. Pathogenic mutations in selenocysteine synthase (SEPSECS) cause neurodevelopmental disorders [31][32][33].…”
Section: Plos Onementioning
confidence: 99%
“…In schizophrenia (SCZ) patients, nonsense de novo mutations of ZNF595 are common. Data from genome-wide association studies suggested that common variants in the ZNF595 gene may be associated with SCZ and SCZ-related traits [30]. Pathogenic mutations in selenocysteine synthase (SEPSECS) cause neurodevelopmental disorders [31][32][33].…”
Section: Plos Onementioning
confidence: 99%
“…This article 1 has been retracted at the request of Authors Xingwang Li and Lin He. After publication, it was realized that approval to use data from the NSFC-NIH Sino-US cooperation project (Project No.…”
mentioning
confidence: 99%